Programming immaterial labour - HARNEY, Stefano (Institutional Knowledge at Singapore Management University, 2006)
Language, image, and ambiance production used to go under the sign of cultural labour. Today, these increasingly gather under the banner of immaterial labour. It is this part of cultural labour, a part of cultural labour most explicitly projecting itself as labour, that I want to discuss in this article.